ANALISIS TINGKAT BAGI HASIL, TINGKAT SUKU BUNGA TERHADAP JUMLAH TABUNGAN DAN JUMLAH DEPOSITO MUDHARABAH PADA BANK MUAMALAT DI INDONESIA - Safitri, Aprilia Dwi; Wuryanti, Prof (PRESTASI, 2013)
ABSTRACTÂ Bank is a very important sector and has considerable influence on economic activity the bank consists of the operations of conventional banks and Islamic banks. The fundamental difference between the two banks is incentive results, where conventional bank interest while implementing Islamic banking system implementing system for the results. The purpose of the study was 1) to determine whether the level of outcome (BI Rate) mudharabah effect on the amount of savings in the Muamalat Indonesia Bank, 2) Determine whether the central bank interest rate (BI Rate) mudharabah effect on the amount of savings in the bank Muamalat Indonesia, 3) know whether the results affect the level of bank deposits in the mudharabah Muamalat Indonesia, 4) Determine whether the interest rate affects the amount of mudharabah deposits in Muamalat Indonesia Bank. The methodology used in this study there are two types of research, research that is descriptive and explanatory research. Research conducted on Muamalat Indonesia Bank, a basis for taking samples with purposive sampling. Sample results are 32 samples. While the methods of analysis used in this study is a multiple linear regression model. The results showed that 1) there is a variable level of influences between the results against mudharabah variable amount of savings in the bank Muamalat Indonesia, 2) Bank interest rate affect the amount of savings mudharabah in BMI, 3) the outcome affect the amount of deposits bankMuamalat mudharabah in Indonesia, and 4) bank interest rate affect the mudharabah deposits in Muamalat Indonesia Bank. Â Key Words : Results against , Interest rate, Savings Mudharabah , Deposit Mudharabah